You only die twice - Gutman, Dan (Gutman, Dan. Genius Files, 2013)
Genius twins Coke and Pepsi McDonald embark on a trip to Graceland and are horrified by the reappearance of their supposedly deceased arch nemesis Dr. Herman Warsaw, who marries their aunt Judy.